Method for improving high charge acceptance and low voltage cycle life capability of auxiliary battery, auxiliary battery and negative lead paste
Patent Information
- Application Number
- CN202611334916.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]第一,负极添加剂的协同效应未被充分挖掘
[0009]本发明的目的在于解决上述现有技术的不足,从而提供一种提升辅助用蓄电池高充电接受及低压循环寿命能力的方法,通过负极“石墨@铅复合材料+高比表面积炭黑+聚丙烯酸(PAA)”三元复合体系和电解液“二氧化硅胶体+硫酸羟胺”双功能添加剂体系,实现了充电接受能力提升50%以上、低压循环寿命提升200%以上的显著效果,有效解决了现有辅助电池在能量回收工况下充电接受不足和低压深循环寿命衰减快的技术难题。
Smart Images

Figure SMS_12 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lead-acid battery technology, specifically relating to a lead-acid battery suitable for low-voltage auxiliary power systems of new energy vehicles. Through composite modification of negative electrode materials and optimization of electrolyte, a technical solution is achieved to significantly improve charging acceptance and low-voltage cycle life. Background Technology
[0002] In recent years, with the rapid development of the new energy vehicle industry, although power batteries adopt solutions such as lithium-ion batteries, vehicles are still generally equipped with 12V lead-acid batteries as low-voltage auxiliary batteries to wake up the high-voltage lithium battery system and power the vehicle's low-voltage electrical equipment. The auxiliary battery needs to continuously power the standby system while the vehicle is parked, and it experiences numerous deep charge-discharge cycles, posing a severe test to its cycle life. Normally, to ensure safety and efficiency, the voltage of the charging system must be strictly maintained within the ideal range of 14.0V to 14.4V. Traditional flooded lead-acid batteries, although performing well at a higher voltage of 15.6V and possessing a long cycle life, are not suitable for the automotive environment. When the voltage drops to the automotive standard of 14.4V, the cycle count decreases rapidly. Simultaneously, in energy recovery braking scenarios, the battery needs to frequently withstand short-term high-current charging, which places extremely high demands on its charging acceptance capability. Short charging times and insufficient charging acceptance capability can easily lead to premature battery failure. To address these technical requirements, existing technologies are mainly improved in the following aspects:
[0003] Regarding negative electrode additives, carbon materials (such as carbon black, graphite, and graphene) have been extensively studied for improving negative electrode conductivity and suppressing sulfation. For example, some studies have used lead sulfate-graphene composite electrode materials added to negative electrode lead paste, utilizing the large specific surface area and high conductivity of graphene to suppress the rise in charging voltage of lead-carbon supercells, enabling pulse charge-discharge cycles to exceed 6000 times. Another technical solution involves adding heterogeneous graphite and composite additives to the negative electrode, achieving a cycle life of over 800 cycles and a capacity retention rate of ≥85%. Carbon black additives have also been proven to effectively suppress negative electrode sulfation and improve charge acceptance. Meanwhile, related technologies have disclosed applications of polyacrylic acid (PAA) or its salts. For example, a patent uses sodium polyacrylate as a component of a negative electrode composite additive, utilizing its high hydrophilicity to form a gel region on the lead surface to improve ion diffusion rate; sulfonic acid-containing acrylic polymers have also been reported to effectively prevent negative electrode sulfation and extend battery life.
[0004] Regarding electrolytes, colloidal electrolyte technology uses silica gelling agents added to dilute sulfuric acid to immobilize the liquid electrolyte into a colloidal state, thereby reducing acid stratification and water loss. Studies have shown that adding a complex of hydroxylamine sulfate and tin dioxide to the colloidal electrolyte can effectively improve the cycle life of colloidal batteries.
[0005] However, the aforementioned existing technologies still have the following shortcomings:
[0006] First, the synergistic effect of anode additives has not been fully explored. Existing technologies mostly focus on the construction of conductive networks using single carbon materials, but there is a lack of systematic research on the complementarity of graphite-based materials and carbon black-based materials in terms of particle size, morphology, and conductivity mechanisms, resulting in low conductive network efficiency. At the same time, the interfacial bonding between carbon materials and lead paste matrix is weak, making them prone to desorption and aggregation during long-term cycling, which accelerates performance degradation.
[0007] Second, the performance bottlenecks of colloidal electrolytes have not been fundamentally resolved. While colloidal electrolytes can mitigate acid stratification, the colloidal network increases ion migration resistance, leading to lower initial battery capacity and reduced charge acceptance. Maintaining the advantages of colloidal electrolytes without sacrificing charging kinetics remains a challenge for the industry.
[0008] Third, the technology is not adequately adapted for the specific application scenario of auxiliary batteries in new energy. Existing improvement solutions are mostly aimed at starting batteries or energy storage batteries, and there is a lack of targeted solutions for the combined performance requirements of auxiliary batteries, namely "high charge acceptance capacity + long low-voltage cycle life". Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method to improve the high charge acceptance and low-voltage cycle life of auxiliary batteries. By using a ternary composite system of "graphite@lead composite material + high specific surface area carbon black + polyacrylic acid (PAA)" for the negative electrode and a dual-functional additive system of "silica gel + hydroxylamine sulfate" for the electrolyte, significant effects are achieved, such as increasing charge acceptance by more than 50% and low-voltage cycle life by more than 200%. This effectively solves the technical problems of insufficient charge acceptance and rapid decay of low-voltage deep cycle life in existing auxiliary batteries under energy recovery conditions.
[0010] A method for improving the high charge acceptance and low voltage cycle life of an auxiliary battery involves introducing graphite@lead composite material, high specific surface area carbon black, and polyacrylic acid into the negative electrode lead paste formulation of the battery, while introducing silica gel and hydroxylamine sulfate into the electrolyte.
[0011] The amount of graphite@lead composite material added is 0.05%-0.5% of the lead powder mass. The preparation method of graphite@lead composite material is as follows: 1-3g of graphite is soaked in 50-100mL of 80% ethanol for 1.8-2.2min, then 200-300mL of 0.05-0.2mol / L lead acetate aqueous solution is poured in, ultrasonicated for 9-11min, filtered, and then the precipitate is washed with deionized water. The washed precipitate sample is immersed in 200-300mL of 0.05-0.2mol / L sodium borohydride, ultrasonicated for 9-11min, filtered, and the precipitate is washed again with deionized water until neutral. It is then dried in an oven at 55-65℃ for 8-12h to obtain graphite@lead composite material.
[0012] The amount of high specific surface area carbon black added is 0.3%-1.0% of the lead powder mass, and the specific surface area is ≥800m². 2 / g.
[0013] The amount of polyacrylic acid added is 0.05%-0.5% of the lead powder mass.
[0014] The electrolyte is composed of It is prepared by adding sulfuric acid solution to silica gel and hydroxylamine sulfate.
[0015] The silica gel is fumed silica, and the amount of silica gel added is 0.5%-3% of the total mass of the electrolyte; the amount of hydroxylamine sulfate added is 0.05%-0.3% of the total mass of the electrolyte.
[0016] Another object of the present invention is to provide an auxiliary storage battery with high charge acceptance and low voltage cycle life, comprising a positive plate, a negative plate, a separator and an electrolyte;
[0017] The negative electrode plate includes a grid and negative electrode lead paste. The mass fraction of each chemical component in the negative electrode lead paste relative to the lead powder is as follows: graphite@lead composite material 0.05%-0.5%, high specific surface area carbon black 0.3%-1.0%, polyacrylic acid 0.05%-0.5%, barium sulfate 0.5%-1.0%, sodium lignosulfonate 0.1%-0.3%, humic acid 0.1%-0.3%, short fiber 0.03%-0.1%, dilute sulfuric acid with a density of 1.38 g / mL 5%-12%, and deionized water 8%-15%.
[0018] The electrolyte is composed of It is prepared by adding sulfuric acid solution to silica gel and hydroxylamine sulfate.
[0019] The preparation method of negative electrode lead paste includes the following steps:
[0020] 1) Weigh each raw material component according to the mass fraction of each chemical component in the negative electrode lead paste relative to the mass of the lead powder in the negative electrode lead paste, and set aside for later use;
[0021] 2) Dry mix lead powder, graphite@lead composite material, high specific surface area carbon black, barium sulfate, sodium lignosulfonate, humic acid, and short fibers for 2-3 minutes;
[0022] 3) Dissolve polyacrylic acid in deionized water beforehand and stir for 2-3 minutes to form a gel solution;
[0023] 4) Next, add the dry mix from step 1) to the adhesive solution from step 2) and wet mix for 3-4 minutes;
[0024] 5) Slowly add dilute sulfuric acid while stirring, controlling the acid addition time to be ≥20min and the temperature to ≤50℃, and mix evenly to obtain lead paste.
[0025] The present invention also aims to provide a negative electrode lead paste, wherein the mass fraction of each chemical component in the negative electrode lead paste according to the mass of the lead powder is as follows: graphite@lead composite material 0.05%-0.5%, high specific surface area carbon black 0.3%-1.0%, polyacrylic acid 0.05%-0.5%, barium sulfate 0.5%-1.0%, sodium lignosulfonate 0.1%-0.3%, humic acid 0.1%-0.3%, short fiber 0.03%-0.1%, dilute sulfuric acid with a density of 1.38 g / mL 5%-12%, and deionized water 8%-15%.
[0026] The negative electrode lead paste of this invention adopts a ternary composite system of "graphite@lead composite material + high specific surface area carbon black + polyacrylic acid (PAA)": The graphite@lead composite material is composed of nano-lead particles deposited in situ on the surface of graphite sheets. The graphite@lead composite material has the high conductivity of graphite, and the large volume of graphite can form sheet conductive surfaces, combining high conductivity network and electrochemical activity; the high specific surface area carbon black forms a three-dimensional conductive supplementary network, connecting the conductive graphite sheets to each other, thereby forming a "point-surface" synergistic conductive system, which greatly increases the conductivity of the lead paste; the introduction of composite carbon material (graphite@lead composite material + high specific surface area carbon black) into the negative electrode improves the conductivity of the lead paste while providing more nucleation sites, which is conducive to refining the grain size of lead sulfate, thereby improving the charge acceptance performance of the battery. On the one hand, polyacrylic acid (PAA) can make the introduced composite carbon material more uniformly dispersed in the lead paste, further improving the charge acceptance performance, and on the other hand, it can enhance the bonding force between the paste and the grid, thereby improving the cycle life of the battery. The electrolyte is a functional colloidal electrolyte containing silica gel and hydroxylamine sulfate. The silica gel network inhibits acid stratification, keeping the plates consistent during battery cycling and significantly improving low-voltage cycle life. Meanwhile, hydroxylamine sulfate acts as a reducing agent, altering the crystal structure of lead sulfate and promoting its reduction, thus improving charge acceptance and maintaining high activity on the negative electrode surface to reduce hydrogen evolution side reactions.
[0027] There is an inherent relationship between a battery's charge acceptance and low-voltage cycle life. Stronger charge acceptance allows for greater charge input within the same timeframe under low-voltage conditions, resulting in better low-voltage cycle life. Actual testing shows that the optimized battery design offers over 50% better charge acceptance and over 200% better low-voltage cycle life compared to conventional batteries. Detailed Implementation
[0028] The present invention first provides a method for improving the high charge acceptance and low voltage cycle life of auxiliary storage batteries. The method involves introducing graphite@lead composite material, high specific surface area carbon black and polyacrylic acid into the negative electrode lead paste formulation of the battery, while introducing silica gel and hydroxylamine sulfate into the electrolyte.
[0029] The addition amount of graphite@lead composite material is 0.05%-0.5% of the lead powder mass. The preparation method of graphite@lead composite material is as follows: 1-3g of graphite is soaked in 50-100mL of 80% ethanol for 1.8-2.2min, then 200-300mL of 0.05-0.2mol / L lead acetate aqueous solution is poured in, ultrasonicated for 9-11min, filtered, and then the precipitate is washed with deionized water. The washed precipitate sample is then immersed in 200-300mL of 0.05-0.2mol / L sodium borohydride, ultrasonicated for 9-11min, filtered, and washed again with deionized water until neutral. The precipitate is then dried in an oven at 55-65℃ for 8-12h to obtain the graphite@lead composite material. The addition amount of high specific surface area carbon black is 0.3%-1.0% of the lead powder mass, with a specific surface area ≥800m². 2 / g. The amount of polyacrylic acid added is 0.05%-0.5% of the lead powder mass. The electrolyte is composed of The electrolyte is prepared by adding sulfuric acid solution to silica gel and hydroxylamine sulfate. The silica gel is fumed silica, and the amount of silica gel added is 0.5%-3% of the total mass of the electrolyte; the amount of hydroxylamine sulfate added is 0.05%-0.3% of the total mass of the electrolyte.
[0030] The present invention also provides an auxiliary storage battery with high charge acceptance and low-voltage cycle life capability, comprising a positive plate, a negative plate, a separator and an electrolyte;
[0031] The specific formula for negative electrode lead paste is as follows:
[0032] Negative electrode lead paste is based on lead powder and contains the following core components:
[0033] (1) Graphite@lead composite material (addition amount is 0.05%-0.5% of the lead powder mass)
[0034] The graphite@lead composite material was prepared by chemical reduction deposition: 1-3g of graphite was soaked in 50-100mL of 80% ethanol for approximately 1.8-2.2min, then poured into 200-300mL of 0.05-0.2mol / L lead acetate aqueous solution, sonicated for 9-11min, filtered, and the precipitate was washed with deionized water. The washed precipitate was then immersed in 200-300mL of 0.05-0.2mol / L sodium borohydride (reducing agent), sonicated for 9-11min, filtered, and washed with deionized water until neutral. The precipitate was then dried in an oven at 55-65℃ for approximately 8-12h to obtain the graphite@lead composite material. This composite material combines the high conductivity network properties of graphene with the electrochemical activity of metallic lead, providing excellent electron transport channels and acting as a "lead framework" to promote the reversible transformation of active substances.
[0035] (2) High specific surface area carbon black (addition amount is 0.3%-1.0% of lead powder mass, specific surface area ≥800 m²) 2 / g)
[0036] The unique chain-like structure of high specific surface area carbon black can form a three-dimensional conductive network in lead paste, creating a "point-to-surface" synergistic conductive system with large-sized graphite@lead composite materials. The high specific surface area also provides more active sites, which helps to suppress the growth of lead sulfate grains in the negative electrode.
[0037] (3) Polyacrylic acid (PAA) (addition amount is 0.05%-0.5% of the lead powder mass)
[0038] As a dispersant and binder, polyacrylic acid (PAA) can effectively improve the dispersion uniformity of graphite@lead composites and carbon black in lead paste, prevent carbon material agglomeration, enhance the bonding force between the paste and the grid, and reduce the shedding of active materials.
[0039] (4) Other conventional additives
[0040] It includes barium sulfate (0.5%-1.0%), sodium lignosulfonate (0.1%-0.3%), humic acid (0.1%-0.3%), short fiber (0.03%-0.1%), and appropriate amounts of dilute sulfuric acid (5%-12%) and deionized water (8%-15%).
[0041] The electrolyte formula is as follows:
[0042] The electrolyte is a colloidal electrolyte system, comprising:
[0043] (1) Dilute sulfuric acid: density is 1.27-1.30 g / cm³.
[0044] (2) Silica gel: Fumed silica is used as a gelling agent, and the amount added is 0.5%-3% of the total mass of the electrolyte to form a stable three-dimensional gel network.
[0045] (3) Hydroxylamine sulfate: The amount added is 0.05%-0.3% of the total mass of the electrolyte. As a reducing agent, hydroxylamine sulfate can change the crystal structure of lead sulfate on the negative electrode and promote its easier reduction to lead during charging, thereby improving the charging acceptance capacity; at the same time, by maintaining the high activity state of the negative electrode surface, it reduces the hydrogen evolution side reaction caused by sulfation accumulation and effectively inhibits gas evolution.
[0046] The present invention also provides an auxiliary storage battery with high charge acceptance and low-voltage cycle life capability, comprising a positive plate, a negative plate, a separator and an electrolyte;
[0047] 3. Battery manufacturing
[0048] (1) Preparation of negative electrode lead paste:
[0049] 1) Weigh each raw material component according to the mass fraction of each chemical component in the negative electrode lead paste relative to the mass of the lead powder in the negative electrode lead paste, and set aside for later use;
[0050] 2) Dry mix lead powder, graphite@lead composite material, high specific surface area carbon black, barium sulfate, sodium lignosulfonate, humic acid, and short fibers for 2-3 minutes;
[0051] 3) Dissolve polyacrylic acid in deionized water beforehand and stir for 2-3 minutes to form a gel solution;
[0052] 4) Next, add the dry mix from step 1) to the adhesive solution from step 2) and wet mix for 3-4 minutes;
[0053] 5) Slowly add dilute sulfuric acid while stirring, controlling the acid addition time to be ≥20min and the temperature to ≤50℃, and mix evenly to obtain lead paste.
[0054] (2) Preparation of positive electrode lead paste: The conventional formula and paste mixing process are used.
[0055] (3) Electrode coating and curing: Conventional coating and curing processes are used.
[0056] (4) Battery assembly and formation: The conventional battery assembly process is adopted. After the battery is assembled, a gel electrolyte is injected, and the finished product is made by one-time formation without acid replacement.
[0057] Example 1:
[0058] The negative electrode lead paste comprises the following components in parts by weight: 1000 parts lead powder, 90 parts deionized water, and a density of... 80 parts sulfuric acid solution, 0.4 parts short fiber, 6 parts barium sulfate, 3 parts sodium lignosulfonate, 2 parts humic acid, 2 parts graphite@lead composite material, and 8 parts high specific surface area carbon black (specific surface area 1000 m²). 2 / g), 2 parts polyacrylic acid (PAA).
[0059] The graphite@lead composite material is composed of graphite and lead. The specific preparation method is as follows: 2g of graphite is soaked in 70mL of 80% ethanol for 2min, then poured into 250mL of 0.1mol / L lead acetate aqueous solution, sonicated for 10min, filtered, and the precipitate is washed with deionized water. The washed precipitate sample is then immersed in 250mL of 0.1mol / L sodium borohydride, sonicated for 10min, filtered, and the precipitate is washed with deionized water until neutral. It is then dried in an oven at 60℃ for 10h to obtain the graphite@lead composite material.
[0060] The electrolyte of the battery is made of The electrolyte is prepared by adding silica and hydroxylamine sulfate to a sulfuric acid solution. The amount of the electrolyte additive is 1 wt% silica and 0.1 wt% hydroxylamine sulfate.
[0061] Example 2:
[0062] The negative electrode lead paste comprises the following components in parts by weight: 1000 parts lead powder, 80 parts deionized water, and a density of... 50 parts sulfuric acid solution, 1 part short fiber, 10 parts barium sulfate, 3 parts sodium lignosulfonate, 3 parts humic acid, 5 parts graphite@lead composite material, and 3 parts high specific surface area carbon black (specific surface area 900 m²). 2 / g), 5 parts of polyacrylic acid (PAA).
[0063] The graphite@lead composite material is composed of graphite and lead. The specific preparation method is as follows: 3g of graphite is soaked in 100mL of 80% ethanol for 1.8min, then poured into 300mL of 0.2mol / L lead acetate aqueous solution, sonicated for 9min, filtered, and the precipitate is washed with deionized water. The washed precipitate sample is then immersed in 300mL of 0.2mol / L sodium borohydride, sonicated for 9min, filtered, and the precipitate is washed with deionized water until neutral. It is then dried in an oven at 65℃ for 8h to obtain the graphite@lead composite material.
[0064] The electrolyte of the battery is made of The electrolyte is prepared by adding silica and hydroxylamine sulfate to a sulfuric acid solution. The amount of the electrolyte additive is 3 wt% silica and 0.3 wt% hydroxylamine sulfate.
[0065] Example 3:
[0066] The negative electrode lead paste comprises the following components in parts by weight: 1000 parts lead powder, 150 parts deionized water, and a density of... 120 parts sulfuric acid solution, 0.3 parts short fiber, 5 parts barium sulfate, 1 part sodium lignosulfonate, 1 part humic acid, 0.5 parts graphite@lead composite material, 10 parts high specific surface area carbon black (specific surface area 950 m²). 2 / g), 0.5 parts of polyacrylic acid (PAA).
[0067] The graphite@lead composite material is composed of graphite and lead. The specific preparation method is as follows: 1g of graphite is soaked in 50mL of 80% ethanol for 2.1min, then poured into 200mL of 0.05mol / L lead acetate aqueous solution, sonicated for 11min, filtered, and the precipitate is washed with deionized water. The washed precipitate sample is then immersed in 200mL of 0.05mol / L sodium borohydride, sonicated for 11min, filtered, and the precipitate is washed with deionized water until neutral. It is then dried in an oven at 55℃ for 12h to obtain the graphite@lead composite material.
[0068] The electrolyte of the battery is made of The electrolyte is prepared by adding silica and hydroxylamine sulfate to a sulfuric acid solution. The amount of the electrolyte additive is 0.5 wt% silica and 0.05 wt% hydroxylamine sulfate.
[0069] Comparative Example 1:
[0070] The negative electrode lead paste lacks graphite@lead composite material and polyacrylic acid (PAA), and uses ordinary acetylene black (specific surface area 60m²). 2 (Approximately / g), the amount added is 2 parts, and the rest is the same as in Example 2.
[0071] The electrolyte of the battery is made of It is prepared by adding sodium sulfate electrolyte additive to sulfuric acid solution, and the amount of electrolyte additive added is 1 wt% sodium sulfate.
[0072] Comparative Example 2:
[0073] The negative electrode lead paste lacks graphite@lead composite material and polyacrylic acid (PAA), and uses ordinary acetylene black (specific surface area 60 m²). 2 (Approximately / g), the amount added is 2 parts, and the rest is the same as in Example 3.
[0074] The electrolyte of the battery is made of It is prepared by adding sodium sulfate electrolyte additive to sulfuric acid solution, and the amount of electrolyte additive added is 1 wt% sodium sulfate.
[0075] 4. Test battery performance
[0076] Using the above Examples 1-3 and Comparative Examples 1-2, 12V (rated C20 of 45Ah) new energy auxiliary batteries were prepared, and the following performance tests were conducted:
[0077] C20: At 25℃±2℃, discharge with current In (2.25A) until the voltage drops to 10.5V.
[0078] -18℃ Low Temperature Start-up: At -18℃±1℃, first discharge with Icc for 30s, and record the voltage U10s after 10s and the voltage U30s after 30s of discharge. Then let it stand for 20s, and then discharge with 0.6Icc for 40s, and record the voltage U90s after discharge.
[0079] 0℃ charging acceptance: The fully charged battery is discharged at 25℃ with a current I0=Ce / 10 for 5h (Ce=the best value among the 3 measured capacities). After discharge, it is placed in an environment of 0℃±1℃ for 15~24h for 10 minutes, and then charged at 14.4V (current limit 100A) for 10min. The current Ica of 10min is recorded.
[0080] -18℃ charging acceptance: The fully charged battery is discharged at 25℃ with a current I0=Ce / 10 for 5 hours (Ce=the best value among the 3 measured capacities). After discharge, it is placed in an environment of -18℃±1℃ for 15~24 hours for 10 minutes, and then charged at 14.4V (current limit 100A) for 15 minutes. The current I15min is recorded for 15 minutes.
[0081] Low-voltage cycle life: At 40℃±2℃, (a) the battery is discharged at 5In (11.25A) for 2 hours; (b) it is charged at a constant voltage of 14.4V (current limited to 5In (11.25A)) for 5 hours; (c) (a)~(b) constitute one cycle, and the cycle ends when the voltage is ≤10V.
[0082] The performance test results of the comparative example and the embodiment are shown in the table below.
[0083]
[0084] Compared to the comparative example, the embodiment shows an improvement of over 50% in charge acceptance performance at 0°C, over 100% in charge acceptance performance at -18°C, and over 200% in low-voltage cycle life. The C20 and -18°C low-temperature start-up performance are comparable to the comparative example, with no decrease. This invention, through optimization of the negative electrode and electrolyte, significantly improves battery charge acceptance performance and low-voltage cycle life while ensuring that other battery performance characteristics are not reduced. It effectively solves the technical problems of insufficient charge acceptance and rapid degradation of low-voltage deep cycle life in existing auxiliary batteries under energy recovery conditions.
Claims
1. A method for improving the high-charge acceptance and low-voltage cycle life capabilities of auxiliary storage batteries, characterized in that: The negative electrode lead paste formulation of the battery incorporates graphite@lead composite material, high specific surface area carbon black, and polyacrylic acid, while silica gel and hydroxylamine sulfate are introduced into the electrolyte.
2. The method for improving the high-charge acceptance and low-voltage cycle life capability of auxiliary storage batteries according to claim 1, characterized in that: The amount of graphite@lead composite material added is 0.05%-0.5% of the lead powder mass. The preparation method of graphite@lead composite material is as follows: 1-3g of graphite is soaked in 50-100mL of 80% ethanol for 1.8-2.2min, then 200-300mL of 0.05-0.2mol / L lead acetate aqueous solution is poured in, ultrasonicated for 9-11min, filtered, and then the precipitate is washed with deionized water. The washed precipitate sample is immersed in 200-300mL of 0.05-0.2mol / L sodium borohydride, ultrasonicated for 9-11min, filtered, and the precipitate is washed again with deionized water until neutral. It is then dried in an oven at 55-65℃ for 8-12h to obtain graphite@lead composite material.
3. The method for improving the high-charge acceptance and low-voltage cycle life capability of auxiliary batteries according to claim 1, characterized in that: The amount of high specific surface area carbon black added is 0.3%-1.0% of the lead powder mass, and the specific surface area is ≥800m². 2 / g.
4. The method for improving the high-charge acceptance and low-voltage cycle life capability of auxiliary batteries according to claim 1, characterized in that: The amount of polyacrylic acid added is 0.05%-0.5% of the lead powder mass.
5. The method for improving the high charge acceptance and long cycle life capability of auxiliary storage batteries according to claim 1, characterized in that: The electrolyte is composed of It is prepared by adding sulfuric acid solution to silica gel and hydroxylamine sulfate.
6. The method for improving the high-charge acceptance and low-voltage cycle life capability of an auxiliary storage battery according to claim 1 or 5, characterized in that: The silica gel is fumed silica, and the amount of silica gel added is 0.5%-3% of the total mass of the electrolyte; the amount of hydroxylamine sulfate added is 0.05%-0.3% of the total mass of the electrolyte.
7. An auxiliary storage battery with high charge acceptance and low-voltage cycle life, characterized in that: Includes positive electrode plate, negative electrode plate, separator and electrolyte; The negative electrode plate includes a grid and negative electrode lead paste. The mass fraction of each chemical component in the negative electrode lead paste relative to the lead powder is as follows: graphite@lead composite material 0.05%-0.5%, high specific surface area carbon black 0.3%-1.0%, polyacrylic acid 0.05%-0.5%, barium sulfate 0.5%-1.0%, sodium lignosulfonate 0.1%-0.3%, humic acid 0.1%-0.3%, short fiber 0.03%-0.1%, dilute sulfuric acid with a density of 1.38 g / mL 5%-12%, and deionized water 8%-15%. The electrolyte is composed of It is prepared by adding sulfuric acid solution to silica gel and hydroxylamine sulfate.
8. The auxiliary storage battery with high charge acceptance and low-voltage cycle life capability according to claim 7, characterized in that: The preparation method of negative electrode lead paste includes the following steps: 1) Weigh each raw material component according to the mass fraction of each chemical component in the negative electrode lead paste relative to the mass of the lead powder in the negative electrode lead paste, and set aside for later use; 2) Dry mix lead powder, graphite@lead composite material, high specific surface area carbon black, barium sulfate, sodium lignosulfonate, humic acid, and short fibers for 2-3 minutes; 3) Dissolve polyacrylic acid in deionized water beforehand and stir for 2-3 minutes to form a gel solution; 4) Next, add the dry mix from step 1) to the adhesive solution from step 2) and wet mix for 3-4 minutes; 5) Slowly add dilute sulfuric acid while stirring, controlling the acid addition time to be ≥20min and the temperature to ≤50℃, and mix evenly to obtain lead paste.
9. A negative electrode lead paste, characterized in that: The mass fraction of each chemical component in the negative electrode lead paste relative to the lead powder is as follows: graphite@lead composite material 0.05%-0.5%, high specific surface area carbon black 0.3%-1.0%, polyacrylic acid 0.05%-0.5%, barium sulfate 0.5%-1.0%, sodium lignosulfonate 0.1%-0.3%, humic acid 0.1%-0.3%, short fiber 0.03%-0.1%, dilute sulfuric acid with a density of 1.38 g / mL 5%-12%, and deionized water 8%-15%.
